A CRITICAL REFLECTION ON THE CHRISTIAN TEACHING ON POLYGAMY IN RELATION TO ITS EFFECT ON THE AFRICAN SOCIETY - Bisong, Peter Bisong; Orji, Modestus Ogonna (Universitas Negeri Makassar, 2020)
The early Christian missionaries have been scathingly accused of uprooting Africans from their historical past and for failing to incorporate African traditional values into Christianity. One of such African traditional values that were booted away by Christianity, is polygamy. Africa is known to have been polygamous but was forced to drop this in favour of Christian monogamy. This paper x-rayed the impact of the Christian doctrine on polygamy on African society and concludes that the practice produces more dysfunctional effects than functional ones. It, therefore, advises the church to revise the one man, one wife doctrine. At best, it should be made optional.